The development of prop-rotor system for 52kg MTOW Quad-Tilt Prop (QTP) UAV - Kim, D.K.; Wie, S.Y.; Kang, H.J.; Kim, T.; Kee, Y.; Lee, M.G.; Yun, C. (My University, 2019)
Electric Drone (UAV) was introduced to public people world widely. Especially the quadcopter which is one type of multi-copters was very popular in people who enjoy personal hobby and leisure. The market required to improve payload and forward flight speed. From this worldwide market trend, KARI had started to pay attention to electric drone (UAV) market such as the high-speed drone which has a capability of vertical takeoff and landing (VTOL). Specially, the drone for observation and reconnaissance purpose gives an impressive attention to government officers, industry and military. For these purposes, KARI decided to develop 52kg MTOW Quad-Tilt Prop UAV (QTP UAV) based on KARI’s existing tilt-rotor technologies. This paper introduces the development of 52kg MTOW QTP UAV and its Prop Rotor system. KARI had experienced rotor system development for over 20 years. KARI had developed the optimized propeller and hub system for this QTP UAV applying optimization of the hover performance and high forward flight speed performance. To develop this prop-rotor system, new propeller’s aerodynamic design and structural design with carbon composite and titanium materials was conducted. For these 3 years development period, KARI had setup the development process of the prop-rotor system with high performance for QTP UAV based on helicopter rotor system’s experience and optimization process.